2013
DOI: 10.1111/aas.12134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of remifentanil on the esophagogastric junction and swallowing

Abstract: Remifentanil may increase risk for gastroesophageal reflux by decreasing the inspiratory EGJ augmentation. The clinical significance of remifentanil-induced swallowing difficulties is to be studied further. Given the limited sample size, it cannot be concluded whether these effects are centrally or peripherally mediated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…Based on this premise and in the context of the biomechanical effects of remifentanil on pharyngoesophageal swallowing that we described previously (27)(28)(29), we hypothesized that exposure to remifentanil results in quantifiable changes in pharyngeal bolus propulsion and UES relaxation and opening, producing knock-on effects, such as increased flow resistance across the UES and overall aspiration risk. To test this hypothesis, we conducted an in-depth analysis of the effects of remifentanil on swallowing function.…”
mentioning
confidence: 91%
“…Based on this premise and in the context of the biomechanical effects of remifentanil on pharyngoesophageal swallowing that we described previously (27)(28)(29), we hypothesized that exposure to remifentanil results in quantifiable changes in pharyngeal bolus propulsion and UES relaxation and opening, producing knock-on effects, such as increased flow resistance across the UES and overall aspiration risk. To test this hypothesis, we conducted an in-depth analysis of the effects of remifentanil on swallowing function.…”
mentioning
confidence: 91%
“…This objective finding is consistent with our clinical experience of patients undergoing anaesthesia, and our previously published 6 Savilampi et al study, showing that remifentanil induces significant swallowing difficulties. 16 An important mechanistic observation emerging from our study was that we detected significant differences between the treatments in relation to one metric in particular, that is, TZn-PeakP, which was selectively shortened during remifentanil exposure. TZn-PeakP measures the latency from maximum bolus distension of the pharyngeal lumen to the time when the pharyngeal constrictors contract maximally.…”
Section: Discussionmentioning
confidence: 66%
“…It has been recently shown that TZnPeakP is shorter in relation to these particular modes of swallow defect. 17 As a corollary to these objective findings, our previous study 16 showed that study participants who reported swallowing problems following remifentanil exposure reported an impaired ability to initiate a swallow. The selective effects of remifentanil in this regard suggest that it may have a greater effect on lingual bolus propulsion and/or pharyngeal swallow trigger, than morphine.…”
Section: Discussionmentioning
confidence: 87%
“…For example, the additional use of opioid receptor antagonism, such as naloxone, would have added to the findings in our study. Of note, previous studies have failed to demonstrate a reversal of the effects of remifentanil by either naloxone or methylnaltrexone; however, a supratherapeutic dose of naloxone may be needed to reverse the effects of remifentanil . When considering remifentanil as a model for mu‐opioid agonism, we acknowledge that the pharmacokinetics of remifentanil is markedly different from that of longer acting mu‐opioids and thus any inference that longer acting mu‐opioid agonists will have similar effects are only an assumption.…”
Section: Discussionmentioning
confidence: 94%
“…Remifentanil is an ultra‐short‐acting mu‐opioid receptor (MOR) agonist, used during anesthesia for its centrally depressing and antinociceptive effects. Many individuals, including healthy volunteers, complain of dysphagia during administration of remifentanil . Recent descriptions of the effects of remifentanil and other MOR agonists on swallowing function have revealed attenuated oropharyngeal and laryngeal sensory function, increased pulmonary aspiration, decreased distal esophageal latency, and decreased esophagogastric junction (EGJ) relaxation .…”
Section: Introductionmentioning
confidence: 99%